2008
DOI: 10.1080/14639220701650842
|View full text |Cite
|
Sign up to set email alerts
|

Threshold shifts and restitution of the hearing after different music exposures

Abstract: Human hearing is sometimes exposed to such high levels at modern musical events that the danger of acute damage cannot be ruled out for musicians, disc jockeys and listeners, even if the exposure time is limited. In order to examine at least basically the hypothetically expected different effects of various musical styles, 10 volunteer test subjects were exposed to three types of music with equally loud lower levels. In a change-over test design over several days, quite different exposures (European and Chines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…Instead, the highest levels of PHT in geophone operators selecting abstract acoustic signals in the noise background less than 65 dB aline with the theory, that the biological effect of noise is not only in its energy but in the content of listened information. For instance, Strasser H. and others showed that listening to the different kinds of music (house music, European and Chinese classical music) with the mean level 94 dBA within an hour, causes different physiological responses [ 25 ]. They found house music characterizing by rhythm, percussion, and a medley to cause significantly longer restitution period and higher accumulated hearing thresholds shifts.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the highest levels of PHT in geophone operators selecting abstract acoustic signals in the noise background less than 65 dB aline with the theory, that the biological effect of noise is not only in its energy but in the content of listened information. For instance, Strasser H. and others showed that listening to the different kinds of music (house music, European and Chinese classical music) with the mean level 94 dBA within an hour, causes different physiological responses [ 25 ]. They found house music characterizing by rhythm, percussion, and a medley to cause significantly longer restitution period and higher accumulated hearing thresholds shifts.…”
Section: Discussionmentioning
confidence: 99%
“…Experimentelle Untersuchungen aus den 70er-Jahren des letzten Jahrhunderts z. B. von Miller (1974) und umfangreiche experimentelle Messungen an größeren Gruppen von otologisch unauffälligen Testpersonen (Details siehe Irle et al 1998Irle et al , 2006 Strasser et al (2007Strasser et al ( , 2008a. Die Anwendung des Halbierungsparameters für extrem hohe Pegel und sehr kurze Wirkzeiten ist absolut unangemessen, weil bei Überschreiten von 120 dB nicht nur mit Vertäubungen, d. h. einer reversiblen Ermüdung des Gehörs, sondern mit akuten irreversiblen Schädigungen gerechnet werden muss.…”
Section: Beispiele Für Höchst Unterschiedliche Wirkungen Energie-äquivalenter Schallbelastungenunclassified
“…The current standard metric, an A-weighted equivalent sound level (L eq ), which often for convenience is translated to a dose (%) value, fails to do so. Recent studies revisiting the physiological damage, by measuring TTS, postexposure to: noise (white, pink brown), varying impulses, music (classical, electronic, heavy metal) show varying levels of physiological stress, despite having the same L eq dB(A) values (Irle et al, 1998;Ordónez and Hammershøi, 2004;Strasser et al, 2008). In the 60's when A-weighting became common practice, along with the 3dB exchange rate, it was known that these where merely necessary approximations due to the complexity of performing the measurements (Johnson et al, 2010).…”
Section: Proposed Dose and Recovery Algorithms Backgroundmentioning
confidence: 99%
“…Recent research revisiting noise exposure and associated physiological costs, through the assessment of temporary-threshold-shifts (TTS), emphasizes that the current damage risk criteria used in noise dosimetry does not adequately represent the associated risk. In order to accurately assess the potential damage, the spectral and temporal characteristics of the noise exposure must be taken into account, yet current metrics fail to do this (Kostek et al, 2012;Strasser et al, 2008).…”
Section: Introductionmentioning
confidence: 99%